Brief Reflections on the Process of European Integration through the Example of Sports Law - Rıfat Tinç, Mehmet (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
This article examines the process of European integration through the lens of EU sports law, using sport as a revealing case study of the Union’s functionalist and progressive integration model. Although sport was traditionally regarded as a non-economic and socially autonomous activity, its growing economic significance has increasingly subjected it to the rules of the EU internal market and competition law. This paper demonstrates that European integration operates asymmetrically in this field: while the Union’s competences remain limited to supporting actions in the non-economic dimension of sport, where sporting activities intersect with economic freedoms, integration is significantly more advanced. Through an analysis of Treaty provisions, EU policy instruments, and the Court of Justice’s evolving case law, the study highlights the spillover effect and pragmatic balancing inherent in EU integration. Ultimately, the EU sports law illustrates how integration extends gradually and flexibly into areas initially outside the core competences of the Union.